Childhood Trauma Aftermath on the Adult BoJack Horseman - Sophie Ariella Tanujaya; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2022)
In recent decades, adult animation has garnered its own audience due to its mix of dark humor and slash of reality. One popular series is BoJack Horseman. The show intrigues me because throughout its six seasons, it manages to show how childhood trauma deeply affects BoJack, the main character, as an adult. In this study, we want to analyze the root causes of BoJack’s childhood trauma and the coping mechanisms he did. The findings of this research suggest that there are two main reasons: maltreatment from caretakers and loss of a loved one. Furthermore, there are four forms of maltreatment from his parents: hurtful words, broken marriage, domestic abuse, and gaslighting/guilt tripping. To cope with his trauma, BoJack used four strategies: escapism, dark humor, suicide attempt, and professional help. Through a combination of these four strategies, BoJack was forced to deal with his childhood trauma to become a better person.